Step-and-Shoot IMRT by Siemens Beams: An EPID Dosimetry Verification During Treatment. (August 2016) - Russo, M.; Piermattei, A.; Greco, F.; Azario, L.; Orlandini, L.; Zucca, S.; Cilla, S.; Menna, S.; Grusio, M.; Chiatti, L.; Fidanzio, A.
Purpose: This work reports the extension of a semiempirical method based on the correlation ratios to convert electronic portal imaging devices transit signals into in vivo doses for the step-and-shoot intensity-modulated radiotherapy Siemens beams. The dose reconstructed at the isocenter point Diso, compared to the planned dose, Diso, TPS, and a γ-analysis between 2-dimensional electronic portal imaging device images obtained day to day, seems to supply a practical method to verify the beam delivery reproducibility. Method: The electronic portal imaging device images were obtained by the superposition of many segment fields, and the algorithm for the Diso reconstruction for intensity-modulated radiotherapy step and shoot was formulated using a set of simulated intensity-modulated radiotherapy beams. Moreover, the in vivo dose-dedicated software was integrated with the record and verify system of the centers. Results: Three radiotherapy centers applied the in vivo dose procedure at 30 clinical intensity-modulated radiotherapy treatments, each one obtained with 5 or 7 beams, and planned for patients undergoing radiotherapy for prostatic tumors. Each treatment beam was checked 5 times, obtaining 900 tests of the ratios R = Diso /Diso, TPS . The average R value was equal to 1.002 ± 0.056 (2 standard deviation), while the mean R value for each patient was well within 5%, once the causes of errors were removed. The γ-analysis of the electronic portal imaging device images, with 3% 3 mm acceptance criteria, showed 90% of the tests with Pγ < 1 ≥ 95% and γmean ≤ 0.5. The off-tolerance tests were found due to incorrect setup or presence of morphological changes. This preliminary experience shows the great utility of obtaining the in vivo dose results in quasi real time and close to the linac, where the radiotherapy staff may immediately spot possible causes of errors. The in vivo dose procedure presented here is one of the objectives of a project, for the development of practical in vivo dose procedures, financially supported by the Istituto Nazionale di Fisica Nucleare.